Metacognitive awareness of pharmacists at different stages of the educational continuum: a comparative study - Zavadskiy, Sergey P.; Materenchuk, Maria Yu.; Sologova, Susanna S.; Bazanova, Galina Yu.; Kashapov, Mergalyas M.; Korol, Ludmila A.; Evgrafov, Alexander A.; Smolyarchuk, Elena A. (Frontiers in Education, 2025)
IntroductionThis study investigates the metacognitive awareness of pharmacy students and pharmacists at various educational stages.MethodsWe compare metacognitive indicators among 2nd and 5th-year students from Sechenov University Institute of Pharmacy and pharmacists undergoing additional professional education at Sechenov University Institute of Postgraduate Education. Metacognitive awareness was assessed using the Metacognitive Awareness Inventory, Evaluation of Metacognitive Knowledge and Activity, and a self-reflection scale.ResultsSignificant differences were found between 2nd and 5th-year students’ metacognitive awareness, with 5th-year students showing higher levels of metacognitive knowledge. Pharmacists undergoing additional education displayed higher metacognitive awareness than undergraduate students, with differences observed in declarative and procedural knowledge, error control, and evaluation.ConclusionCognitive and regulatory metacognitive indicators develop throughout the educational continuum, emphasizing the need to cultivate reflexive qualities in future pharmacists. Tailored approaches for improving metacognitive abilities among pharmaceutical specialists are essential. Further exploration of the motivational aspect of metacognitive awareness in pharmacy education is warranted.